Clinical Implications of Social Anxiety Disorder (SAD) and its Detection Methods- A Systematic Review - Dian Pitaloka Priasmoro; Yuni Asri (Journal of Nursing Practice)
Background: A common symptom of SAD is significant impairment in interpersonal relationships that can affect various aspects of life as well as daily functioning and lead to decreased quality of life. Individuals with high social anxiety will tend to withdraw from social environments.